Pharmacology of Cenobamate: Mechanism of Action, Pharmacokinetics, Drug–Drug Interactions and Tolerability - Roberti, Roberta; De Caro, Carmen; Iannone, Luigi Francesco; Zaccara, Gaetano; Lattanzi, Simona; Russo, Emilio (CNS drugs, 2021)
Cenobamate is one of the latest antiseizure medications (ASMs) developed for the treatment of focal onset seizures in adult patients. The recommended starting dose is 12.5 mg/day, titrated gradually to the target daily dose of 200 mg, which may be increased to a maximum of 400 mg/day based on clinical response. Although the high rate of seizure freedom observed in randomized, placebo-controlled clinical trials has resulted in exciting expectations, further clinical studies are needed to better define its clinical profile. Cenobamate is characterized by a peculiar pharmacology regarding both pharmacodynamics and pharmacokinetics. The mechanism of action has only partly been described, with the drug acting on voltage-gated sodium channels through a pronounced action on persistent rather than transient currents. Cenobamate also acts as a positive allosteric modulator of GABA A receptors independently from the benzodiazepine binding site. The bioavailability of cenobamate is not influenced by other drugs, except phenytoin; it can inhibit cytochrome P450 (CYP) 2C19 and induce CYP3A4 and 2B6, and hence can potentially interact with many drugs (e.g. dose adjustments may be required for lamotrigine, carbamazepine and clobazam). The pharmacokinetics of cenobamate are not linear and dosage increases imply a disproportional increase in plasma levels, particularly at doses higher than 300 mg. The most common and dose-related adverse effects associated with cenobamate include central nervous system-related symptoms, mainly somnolence, dizziness, diplopia, and disturbances in gait and coordination. A somewhat higher incidence of adverse events has been observed in patients concomitantly treated with sodium channel blockers. The most relevant safety issues are currently represented by the risk of severe skin reactions (apparently avoidable by a slow titration) and QT shortening (the drug is contraindicated in patients with familial short QT syndrome or taking QT-shortening drugs). Overall, cenobamate is a promising ASM with an intriguing and not fully understood mechanism of action; pharmacokinetic issues need to be considered in clinical practice.